Prevalence and Bilateral Occurrence of First Permanent Molar Caries in 12-Year-Old Students - Mostafa Sadeghi (Tabriz University of Medical Sciences, 2007)
Background and aims. Dental caries is one of the most prevalent chronic diseases in children and DMFT index is the most important quantitative factor for measuring tooth health. The purpose of the present study was to determine prevalence and bilateral occurrence of first permanent molar caries in 12-year-old Iranian students. Materials and methods. This cross-sectional study was carried out on 563 twelve-year-old students (307 boys and 256 girls), randomly selected from private and public schools of Rafsanjan, Iran, in 2006. All students were examined clinically for dental caries using the World Health Organization (WHO) criteria by a specialist on a dental chair in Rafsanjan Dental School. Data was analyzed using chi-square and t-test. Results. The mean DMFT score of first permanent molars was 1.9 ± 1.6 (1.83 boys, 1.98 girls) and 31.4% (32.9% boys, 29.7% girls) of the students were caries free. There were no significant differences between boys and girls. Decayed (D) component yielded to be 40.9%, missing (M) 0.35% and filled (F) 6.22%. Maxillary and mandibular first permanent molars had 80.8% and 84% bilateral caries occurrence, respectively. There were no significant differences between the caries prevalence of right and left sides. Conclusion. Caries prevalence among 12-year-old students in Rafsanjan, Iran is less than the global standards of WHO and FDI for 2000, but close to the gold standard for 2010. Bilateral caries occurrence in the first permanent molars was concluded to be high in the study population.